Molecular cloning, characterization, and promoter analysis of vitamin E biosynthetic genes from the oil palm - Kong, Sze Ling (2013)
Tocopherols and tocotrienols, commonly known as vitamin E, play a crucial role in human and animal nutrition. In recent years, tocotrienols have been reported as a powerful antioxidant agent and linked with various potential health benefits such as antiangiogenic properties exhibited by palm tocotrienols. Therefore this brings the interest to carry out isolation and characterization of vitamin E biosynthetic genes from the oil palm (E. guineensis and E. oleifera) since crude palm oil has been well known to be the richest source of tocotrienols in nature. Homogentisate geranylgeranyl transferase (HGGT) and homogentisate phytyltransferase (HPT) are the two key enzymes that catalyse the condensation of homogentisic acid (HGA) with a prenyldiphosphate to produce tocotrienols and tocopherols in plants, respectively. The partial cDNAs encoding HGGT and HPT enzymes were successfully isolated from both oil palm species by PCR amplification using degenerate primers. Subsequently, full length cDNA sequences were obtained by rapid amplification of cDNA ends (RACE) using genespecific primers. The full length deduced amino acid sequences were further analyzed using various bioinformatics tools available publicly. The analysis revealed the presence of an UbiA prenyltransferase conserved domain in all four protein sequences and suggested that oil palm HGGT and HPT are more evolutionarily related with their counterparts from other monocot plant species based on the result from homologous alignment and phylogenetic analysis. Next, quantitative gene expression analysis was carried out to elucidate the transcript profiles of the oil palm HGGT and HPT genes in different tissues and at different developmental stages of the mesocarp by real-time PCR. Two reference genes that showed to be stably expressed in each experimental set were identified using geNorm software. The expression level of each target gene in each experimental sample was subsequently determined by normalizing to the two validated reference genes. Overall result showed that the oil palm HGGT and HPT transcript production is spatially and temporally regulated. The HPT gene was constitutively expressed in all tested tissues except in 15 w.a.a kernel whereas oil palm HGGT gene showed preferential expression in mesocarp and kernel tissues and highly expressed when active oil deposition occurred in 17 w.a.a mesocarp. This indicates that HGGT expression is regulated by the oil synthesis process in palm fruits. Lastly, genome walking PCR successfully amplified the HGGT promoter region of both oil palm species. By searching in PLACE, PlantCARE and PlantPAN databases, a number of important cis-regulatory elements were found and comparison between these data has resulted in the identification of several common motifs which may be involved in coordinating expression of these genes. The motifs basically can be divided into four main groups including phytohormone-responsive, light-responsive, abiotic factorresponsive and endosperm specificity. This suggests that the regulation of HGGT expression in E. guineensis and E. oleifera involved many similar factors. Further characterization of the potential important motifs would facilitate better understanding on the regulatory mechanism of tocotrienol synthesis in oil palm at the molecular level.